PENGARUH VARIASI METERING STROKE TERHADAP CACAT PRODUK CETAKAN INJEKSI PLASTIK - Rahman Hakim; Amar Makruf; Ahmad Nurasa; Widodo Widodo; Irvan Wahyudi (Jurnal Teknologi Terapan, 2020)
The research aims to analyze the effect of metering stroke on product quality. Metering strokes relate to product weight and mold capacity. The material used is Polyamide (Nylon) 66, using an ENGEL 50ton capacity Injection Molding machine.  The research method used is an experimental method before mass pre-production with stroke metering variation as a production parameter. A normality test was used to investigate the experimental data. Shapiro-Wilk's formula on Minitab® software was used to process the data. Product defects caused by an improper metering stroke often in the injection process are short mold and flashing prints. The results show that short mold production defects occur when the metering stroke is 60 mm due to the material does not fill the full cavity. Furthermore, flashing occurs when the metering stroke is 70 mm due to out of cavity capacity. Therefore, the appropriate parameter is a 65 mm metering stroke with good quality part results.